Biochemical and Physiological Metabolic Pathways Effects of Obesity in Women. A Comparative Clinical Study - Mohammad Israr, Fayaz Ahmed Memon, Misdaq Batool, Hafiz Fahad Ullah Saeed, Nouman Aziz, Shahzad Khan Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and Objectives: The objectives of this study were to identify the negative effects of obesity and provide health awareness to obese women for healthy and active life. Methodology: This was a clinical study and 200 women were selected and divided them into different groups. BMI, systolic and diastolic blood pressure, random glucose levels, serum cholesterol, triglycerides, low density lipoprotein (LDL), high density lipoprotein (HLD) and uric acid levels were measured. The collected raw data of all women of group-A and group-B were represented bio-statistically by applying SPSS-version 2021. All the biomarkers were presented through mean standard deviation and significant (p<0.005) regression t-test of one way ANOVA. Results: The results of present study were significant (p<0.005). The random blood serum levels of glucose, uric acid, cholesterol, triglycerides, low density lipoprotein and high density lipoprotein of group-B were (157.04± 10.12, 12.10±10.02, 220.14± 10.11, 180.10± 10.02, 150.20± 10.6, and 60.01± 1.10) which showed a remarkable changes than control group respectively. Conclusion: Worldwide, the number of obese people is rising at an alarming rate. Present study described the negative effects of obesity in women. The findings of this study were an indication for obese women regarding life threatening medical complications because of their overweight.